'A high degree of understanding and tolerance': veranderende denke oor die moderne gereformeerde kerklied - Kruger, D. (Koers, 2007)
'A high degree of understanding and tolerance': changing thoughts on the modern reformed church song Currently, churches worldwide are experiencing an unparalleled increase in new hymns. Consequently, the requirements of the modern congregational song are much more challenging and demanding. Although the principles of music theory remain a primary criterion for the evaluation of the congregational song, aspects concerning the spiritual requirements, musical taste and culture of the modern church member are becoming increasingly relevant when thinking about the congregational song. In this article the author gives a general overview as to the nature of the modern church song against the background of liturgical renewal within the reformed tradition. The profile of the postmodern church member as regards spiritual needs, musical taste and culture is outlined and connected with the current sensitivity of spirituality and emotional experience through worship and song. Lastly a connection is made between the current trends of hymnological thought and the reformed principles. It is argued that greater tolerance and understanding can lead towards a reforming, rather than a reformed attitude towards the modern congregational song. The discussion is illustrated with examples from the “Liedboek van die kerk” (2001).